Palaeoenvironmental reconstruction in South Africa's year-round rainfall zone using multiproxy geochemical analyses on lake sediments from Swartvlei - Maboya, Matjie Lillian (Department of Environmental and Geographical Science, 2020)
Coastal lakes in the south coast of South Africa contain sediments with good records of palaeoenvironmental changes. Swartvlei is the largest of the lakes in the Wilderness Embayment and is connected to the Indian Ocean via an estuary. The lake is believed to have been formed during sea-level regressions in the quaternary, and separated from Groenvlei lake between 4000 and 2000 cal BP. There are questions about dominant precipitation regimes as well as the onset, cessation and altitude of marine transgressions in the area. In this study, Holocene sediments from Swartvlei Lake were extracted and investigated using multiple methods. These include organic and inorganic geochemical proxies and multidating approach through radiocarbon and OSL dating. A composite profile was made using marker layers with lithostratigraphic distinctions combining three cores into one continuous, 7 m long core spanning 8600 cal BP. The core was subdivided into two distinct zones namely, Unit A (8600 to 3500 cal BP) and Unit B (3500 cal BP to present), identified using cluster analysis on particle size data. The results reveal low sea-levels with limited precipitation and aquatic productivity during the early Holocene, followed by a marine incursion from 4500 to 3500 cal BP and moister conditions thereafter. This marine incursion, marked by increased Ca and TIC concentrations, occurred when the physical barriers were breached, and the estuarine channel widened due to a landward strandline migration. Pronounced riverine input due to increased precipitation was observed after 3500 cal BP, with strong minerogenic input and lowered sealevel. An influx of silt and clay material that dominate the top half of the core marks Swartvlei’s evolution into more lacustrine conditions and its separation from Groenvlei during the same period. A more humid climate is further inferred from organic proxies that indicate a greater in-wash of vascular vegetation during this period, as well as higher productivity from 3500 to 1400 cal BP. In addition, high biogenic silica concentrations indicate increased bio-productivity during the Little Ice Age (LIA) while increased sedimentation rates suggest that anthropogenic activity impacted the lake from 150 cal BP. This study adds insight to the geomorphic evolution of Swartvlei and highlights the usefulness of geochemical analyses in the elucidation of regional quaternary environmental and climatic changes.